2021
DOI: 10.3389/fimmu.2021.631271
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kδ Forms Distinct Multiprotein Complexes at the TCR Signalosome in Naïve and Differentiated CD4+ T Cells

Abstract: Phosphoinositide 3-kinases (PI3Ks) play a central role in adaptive immunity by transducing signals from the T cell antigen receptor (TCR) via production of PIP3. PI3Kδ is a heterodimer composed of a p110δ catalytic subunit associated with a p85α or p85β regulatory subunit and is preferentially engaged by the TCR upon T cell activation. The molecular mechanisms leading to PI3Kδ recruitment and activation at the TCR signalosome remain unclear. In this study, we have used quantitative mass spectrometry, biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 88 publications
(121 reference statements)
0
23
0
Order By: Relevance
“…It has been reported that IQGAP3 can be used as a potential antigen for PRAD mRNA vaccine development and is associated with immunity [ 33 ]. In addition, activated T cells upregulated IQGAP3 through PI3K δ [ 37 ]. To further understand the role of IQGAP3 in tumor immunity, we evaluated the correlation between IQGAP3 expression and various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IQGAP3 can be used as a potential antigen for PRAD mRNA vaccine development and is associated with immunity [ 33 ]. In addition, activated T cells upregulated IQGAP3 through PI3K δ [ 37 ]. To further understand the role of IQGAP3 in tumor immunity, we evaluated the correlation between IQGAP3 expression and various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Cbl-interacting protein of 85 kDa (CIN85) is a protein expressed in many different cell types, involved in processes as diverse as cytokinesis, lysosomal degradation of the epidermal growth factor receptor, , clathrin-mediated receptor internalization, cell adhesion and cytoskeletal remodeling, , and both T cell receptor and B cell receptor (BCR) signaling. In the context of processes associated with BCR signaling, CIN85 was shown to be constitutively associated with Src homology 2 domain-containing leukocyte protein of 65 kDa (SLP65), engaging in promiscuous multivalent interactions between its Src-homology 3 (SH3) domains and SLP65 proline-rich motifs (PRMs) . By association with small unilamellar phospholipid vesicles via the N-terminal domain of SLP65, all these transient interactions lead to the formation of droplets showing characteristics of liquid–liquid phase separation (LLPS). , These organelles form in the resting state of the B cell and provide preformed complexes of CIN85 and SLP65, which allow for an accelerated cellular response upon BCR engagement .…”
Section: Introductionmentioning
confidence: 99%
“…By association with small unilamellar phospholipid vesicles via the N-terminal domain of SLP65, all these transient interactions lead to the formation of droplets showing characteristics of liquid–liquid phase separation (LLPS). , These organelles form in the resting state of the B cell and provide preformed complexes of CIN85 and SLP65, which allow for an accelerated cellular response upon BCR engagement . Notably, CIN85 is involved in the preassembly of effectors in resting T cells as well, but this involves a distinctly different set of interaction partners compared to B cells . Besides being necessary for the formation of droplets together with SLP65 in the resting state of the B cell, CIN85 itself also promotes higher-order structures: its C-terminal coiled-coil domain exhibits a high propensity for trimerization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13,14 ] In addition, PI3Kδ expeditiously collaborates with many adaptor proteins including GAB3 in the process of CD4 + T cell activation, which performs a vital role in adaptive immunity by signal transduction. [ 15 ] Likewise, a recent study has found that GAB3 is involved in the activation of macrophage and CD8 + T cell in the management of chronic colitis. [ 16 ] Recent studies have identified that GAB3 exerts essential biological functions in multiple cancers, including ovarian cancer, [ 17 ] colorectal cancer, [ 18 ] and glioma.…”
Section: Introductionmentioning
confidence: 99%